2023
DOI: 10.1021/acsomega.2c06942
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Multicolor Biomass Carbon Dots Based on Solvent Control and Their Application in Cr(VI) Detection and Advanced Anti-Counterfeiting

Abstract: Multicolor fluorescent carbon dots (CDs) have received widespread attention due to their excellent fluorescence performance and promising prospects in anti-counterfeiting and sensing detection. To date, most of the multicolor CDs synthesized are derived from chemical reagents; however, the overuse of chemical reagents during the synthesis process will pollute the environment and limit their application. Herein, multicolor fluorescent biomass CDs (BCDs) were prepared by a one-pot ecofriendly solvothermal method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…As the excitation was removed, due to the different fast and slow lifetimes of the blue emission on composites, some of the word letters disappeared, and after only 25 s the final word "on" was revealed, corresponding to the slower blue emitting composites (CDs@SiO 2 -600, and CDs@SiO 2 -550). A similar strategy was applied to a QR code, in which the composites (CDs@SiO 2 -600, and CDs@SiO 2 -550) were used only in certain areas of the code, to produce an unreadable code, which turned into a complete code after 20 s. [85] In another work with a green approach scheme, Wang et al [101] prepared a CDs solution by a solvothermal treatment of spinach as carbon precursor in water (BCD1), ethanol (BCD2), acetone (BCD3), and a mixture of the last two (BCD4). The four samples exhibited strong absorption bands in the UV region (240-280 nm) corresponding to the 𝜋→𝜋* electronic transition of the C═C bond.…”
Section: Carbon Dots For Anticounterfeiting Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the excitation was removed, due to the different fast and slow lifetimes of the blue emission on composites, some of the word letters disappeared, and after only 25 s the final word "on" was revealed, corresponding to the slower blue emitting composites (CDs@SiO 2 -600, and CDs@SiO 2 -550). A similar strategy was applied to a QR code, in which the composites (CDs@SiO 2 -600, and CDs@SiO 2 -550) were used only in certain areas of the code, to produce an unreadable code, which turned into a complete code after 20 s. [85] In another work with a green approach scheme, Wang et al [101] prepared a CDs solution by a solvothermal treatment of spinach as carbon precursor in water (BCD1), ethanol (BCD2), acetone (BCD3), and a mixture of the last two (BCD4). The four samples exhibited strong absorption bands in the UV region (240-280 nm) corresponding to the 𝜋→𝜋* electronic transition of the C═C bond.…”
Section: Carbon Dots For Anticounterfeiting Applicationsmentioning
confidence: 99%
“…Reproduced under terms of the CC‐BY‐NC‐ND 4.0 license. [ 101 ] Copyright 2023, American Chemical Society. E) Anticounterfeiting patterns (left under sunlight; right under UV light) Reproduced with permission.…”
Section: Carbon Dots For Anticounterfeiting Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The team used the as-synthesized carbon dots for the anticounterfeiting and the sensing of Cr 6+ . 109 Tariq et al reported microwave-assisted fig biomass extracted red emissive carbon dots, which exhibited excellent antibacterial properties and were used as a antibacterial agent for the diagnosis of bacterial infection. 110 Yang et al developed glutathione-supported waste tobacco leaf-derived red emissive fluorescent carbon dots via a simple hydrothermal method.…”
Section: Synthesis Of Red-emitting Fcnmsmentioning
confidence: 99%
“…Using three natural biomasses, honeysuckle, turmeric and perilla leaves, respectively, as precursors, Zhao et al 40 prepared blue, green and red carbon nanodots by an ultrasound-assisted method at room temperature, which can be used effectively in bacterial imaging. Wang et al 41 synthesized four biomass CDs (BCDs), blue, crimson, grayish white, and red, with QYs of 8.9%, 12.3%, 10.8%, and 14.4%, respectively, by varying the reaction solvents using green spinach leaves as the carbon source. The results revealed that changes in the boiling point and polarity of solvents altered the carbonation process of polysaccharides and chlorophylls in spinach, which further led to changes in particle size, surface functional groups and porphyrin luminescence properties.…”
Section: Introductionmentioning
confidence: 99%